Economia circular: Repensando estratégias no comércio internacional - Jennyfer Ferreira da Silva; Michelle Márcia Viana Martins (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
This study explores the intersection between circular economy (CE) and international trade (IT), highlighting the potential of trade policies and instruments to promote CE on a global scale. The text addresses, directly or indirectly, four fundamental questions: how CE promotes IT, how IT promotes CE, how CE hinders IT, and vice versa. CE promotes IT by creating demand for green technologies, recycling services, and remanufactured products, which can be supplied by other countries, especially through the integration of circular practices into global value chains (GVCs). This integration can facilitate reverse logistics and the exchange of recyclable materials, making supply chains more efficient and resilient. Trade liberalization facilitates the import of recycled and remanufactured materials, stimulating reuse and recycling on a global scale. For this, international cooperation, the development of multilateral and regional agreements, and the harmonization of technical standards are crucial to integrating circular practices across regions. IT hinders CE through unnecessarily strict standards and regulations without scientific evidence, which can create trade barriers and increase compliance costs for companies operating in multiple markets. Furthermore, specific labeling requirements, certifications, and quality standards for recycled products can hinder integration into GVCs, especially for developing countries with limited regulatory capacity. Finally, IT can harm CE by facilitating the export of waste to countries with weaker environmental regulations, leading to pollution and public health issues. Additionally, dependence on imported raw materials, lack of incentives for reuse and recycling, and the complexity of regulations on waste and remanufactured products can perpetuate linear production and consumption practices. The conclusion emphasizes the importance of international cooperation, the harmonization of standards, and the promotion of trade policies that encourage sustainable practices, ensuring that CE and IT can coexist and mutually reinforce each other in the pursuit of sustainable economic development.
Keywords: F18; Q56; Q58; 330; non-tariff measures; recycling; trade policies; environmental measures